Impact And Development Of Online Education (E- Learning) In India - Joshi, Piyush; Dewangan, Dr. Shweta (The journal of contemporary issues in business and government, 2021)
Over a period of time it is found that different sectors of economy have changed including education sector. Unlike any other sector, education sector has seen many evolution and changes. Education system changed from Guru-Shishya Parampara to class room teaching, then teaching with the help of projectors or LED and now its online teaching classes or teaching through E-Learning portals or Web Based E-Learning (WBEL). It has been seen from the past several years that online education system or E- Learning system has emerged as a powerful contender for new education system. From the recent past it has been found that several online courses have been conducted to educate millions of people around the globe on various topics. In spite of difference in culture and language and diverse population E-Learning system has gained a lot of popularity increase in affordability and purchasing power of Indians. The only reason for growth in E- Learning system is drastic change in information technology and technological improvements. This article aimed at examining the impact of E-Learning or Web Based E- Learning (WBEL) in modern India Education System.